Analysis of consumption of medical resources in terms of intensive care unit/hospital stay and severity using Japan Trauma Data Bank. Issue 4 (28th March 2016) - Oda, Jun
Abstract : Aim: We analyzed the length of intensive care unit or hospital stay of trauma patients to assess the consumption of medical resources using the Japan Trauma Data Bank. Methods: We classified 60, 580 cases registered between 2004 and 2010 in the Japan Trauma Data Bank by hospital ward on emergency admission. Results: A total of 9, 564 intensive care patients could be moved to the general ward before hospital transfer or discharge; 6, 217 cases were transferred to another hospital and 9, 444 cases were discharged directly from the intensive care unit. The length of intensive care unit or hospital stay correlated with the injury severity score. There were 5, 856 patients (68%) from the non‐survivors who died within 3 days of admission. Conclusion: Based on the Japan Trauma Data Bank data for many trauma patients, there are numerous cases of long‐term stay ≥15 days in intensive care in patients who could not be transferred to a general ward and who consumed the medical resources in the critical care department.